STAND-ALONE PV PUMPING SYSTEM ADJUSTMENT BY VALVE-THROTTLING CONTROL - HACHEMI, AMMAR; BOUZIANE, MOHAMED TEWFIK (Courrier du Savoir, 2016)
Stand-alone photovoltaic water pumping system is one of the best choices, especially in remote areas. In the most cases, the photovoltaic energy is used directly from photovoltaic panels without conversion or battery storage. The particularity of pumps installed along the sun, that their characteristics (flow rate, head, power, rotation speed) depends on solar irradiations which varies over the days and seasons of the year. Pumps installed in this system have to be controlled to keep them working in the best efficiency and with the required flow rate. Valve-throttling control is one of control methods commonly used to adjust and to control the flow rate in pumping systems. This method has a direct impact on pump performances (power consumption, amount of water delivered, efficiency...) and its operating point. In this paper, we show a laboratory test of the centrifugal solar pumps, where their characteristics were determined by the valve-throttling control. Comparing the results obtained with those given by the manufacturer, we note a considerable loss in the head and energy which can be treated in this study.